Determination of the Origin of Mukdadiya Formation’s Gravels in Al-Teeb Region, East of Maysan Governorate, Southern Iraq, Based on Sedimentological and Paleontological Evidence - Mahdi, Maher M.; Soltan , Basim H. (Iraqi Journal of Science, 2021)
Mukdadiya Formation represents one of the formations that cover a huge area of Iraq. It contains several clastic deposits, such as sandstone, siltstone, and a noticeable amount of gravels. The gravels are considered as the hallmark to differentiate between Injana and Mukdadiya formations. Therefore, the current study focused on these facies to determine the petrography, paleontology , and origin of Mukdadiya deposits. The results of SEM-EDX and XRD analyses showed two types of gravels, namely the siliceous and lime gravels. The highest percentage of gravels belonged to the sedimentary origin (limestone). The elements of Si, Ca, and Fe represented the common elements that formed the studied gravels. The paleontological study displayed numerous fossils that are composed of these gravels, belonging to several groups, including foraminifera, radiolaria, dinoflagellata, echinoida, gastropoda, and calcisphera. Also, four microfacies were identified in the studied gravels. After comparison of all collected data with selected formations, the results confirmed that the origin of the derived gravels is from the Qulqula Formation, because of their content of radiolaria and the other characterizing fossils.